We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
63
3
avatar

Let f(x)=x+1 and g(x)=2x. Also denote the inverses to these functions as f^-1 and g^-1. Compute \( \[f(g^{-1}(f^{-1}(f^{-1}(g(f(5)))))).\]\)

 Jul 13, 2019
 #1
avatar
0

find f^-1 =                y = x+1    solve for x and then switch x and y's     x = y-1     so  f^-1 = y = x-1

 

find g^-1                  y = 2x    solve for x   x = y/2    switch y's and x's    y = x/2  = g^-1

 

 

Now f(5) (this is the original f(x) function....not thte inverse)   f(5) = 5+1 = 6

  then  g(6) = 2x = 2(6) = 12

   then f^-1  (12) = 11

    then  f^-1 (11) = 10

      then g^-1 (10 ) = 5

       then f (7) =

 Jul 14, 2019
 #3
avatar+18754 
0

Problems posting   (internal server error)  ... corrected last step in answer below....   ~EP

ElectricPavlov  Jul 14, 2019
edited by ElectricPavlov  Jul 14, 2019
edited by ElectricPavlov  Jul 14, 2019
 #2
avatar+18754 
+1

find f^-1 =                y = x+1    solve for x and then switch x and y's     x = y-1     so  f^-1 = y = x-1

 

find g^-1                  y = 2x    solve for x   x = y/2    switch y's and x's    y = x/2  = g^-1

 

 

Now f(5) (this is the original f(x) function....not thte inverse)   f(5) = 5+1 = 6

  then  g(6) = 2x = 2(6) = 12

   then f^-1  (12) = 11

    then  f^-1 (11) = 10

      then g^-1 (10 ) = 5

       then f (5) = 6

 Jul 14, 2019
edited by ElectricPavlov  Jul 14, 2019
edited by ElectricPavlov  Jul 14, 2019

16 Online Users

avatar